Pemberdayaan Kader Posyandu untuk Optimalisasi Kesehatan Ibu Hamil dengan Risiko Tinggi di Kampung Sambawofuar - Fitriani Fitriani; Maria Asyerem; Chiana Endemina Bonsapia; Inggrit Rita Uli Manik (Lembaga Pengembangan Kinerja Dosen, 2025)
Sambofuar Village in Samofa District, Biak Numfor Regency, faces various maternal health challenges due to limited access to healthcare services, low socioeconomic conditions, and inadequate capacity of posyandu cadres in supporting pregnant women with high-risk conditions. With a population of 954 people and 228 households, only 64% of pregnant women received antenatal care during the second trimester, while 18% did not undergo any pregnancy check-up. To address these issues, the Student Creativity Program was implemented using a community-based cadre empowerment approach. The program was carried out from October 11 to December 9, 2024, involving five posyandu cadres, most of whom were 50–59 years old, had an elementary school education, and had more than five years of experience. The intensive training provided resulted in a significant increase in knowledge, where pre-test scores ranging from 30–50 improved to 70–90 in the post-test. Mentoring activities at the posyandu also showed that all cadres (100%) were able to perform their duties effectively, including providing health education and independently assisting high-risk pregnant women. This program has contributed positively by improving cadre competency, strengthening maternal health literacy, and potentially reducing the risk of pregnancy complications. Overall, cadre empowerment through training and education has proven effective and should be continued to strengthen the maternal health system in Sambofuar Village.